Associations between dietary patterns and an array of inflammation biomarkers and plasma lipid profile in postmenopausal women - Bolaji L. Ilesanmi-Oyelere; Marlena C. Kruger (BMC, 2023)
Abstract Objective and design In this cross-sectional study, evaluation of the association between four dietary patterns, nutrients and food intakes and an array of systemic inflammation biomarkers and lipid profile among 80 New Zealand postmenopausal women were conducted. Materials Eighty postmenopausal women participated in the study. A validated food frequency questionnaire was used to collect nutrients and food intake. Four dietary patterns were identified by principal component analysis (PCA) and plasma samples collected for inflammatory biomarkers and lipid profile measures. Results There were negative correlations between intake of dietary fibre, soluble and insoluble non-starch polysaccharides (NSP), vitamin C and niacin and with almost all the inflammatory markers for the whole group. Vegetables, tea/coffee and especially fruit intake were negatively correlated with the inflammatory biomarkers in the whole group. A high intake of Pattern 1 (potato, bread, and fruit pattern) was associated with a low risk of high interferon (IFN)-α2, IFN-λ, interleukin (IL)-6 and IL-8 levels while a high intake of Pattern 3 (fast-food pattern) was associated high risk of IFN-α2 levels. Multiple linear regression showed a negative correlation between Pattern 2 (soups and vegetables pattern) and levels of C-reactive protein (CRP) as well as ferritin. A positive association was observed between Pattern 3 (fast-food pattern) and CRP levels. Positive correlation was also observed between Pattern 2 and high-density lipoprotein (HDL) and total cholesterol (TC) levels, Pattern 4 (meat and vegetables pattern) was however negatively correlated with TC, low-density lipoprotein (LDL) and TC/HDL ratio. Conclusions The result of this study reinforces the contribution and role of diet in modifying inflammation in postmenopausal women.